2010
DOI: 10.1143/jjap.49.055701
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Incorporating Rare Earth Metals on the Schottky Barrier Height of Ni Silicide

Abstract: We study the elastic scattering of positronium atoms by hydrogen atoms at medium energies using partial-wave Born-Oppenheimer (BO) exchange amplitudes and report accurate BO cross sections in the energy range 0 to 60 eV. The present BO results agree with a 22-state R-matrix and a five-state coupled-channel model potential calculation, but disagree strongly with a conventional close-coupling calculation as well as its input BO amplitudes at medium energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
(27 reference statements)
0
9
0
1
Order By: Relevance
“…PtSi is a promissing contact material for PMOS source and drain, because of its excellent thermal stability, low Si consumption and low SBH for hole. However, the barrier height for electron (Φ Bn ) is 0.87 eV, which is relatively high compared to that of NiSi [3,5]. PtSi alloying with low work function metal is a promissing process to reduce Φ Bn , and we have reported that a 0.3 eV reduction of Φ Bn , was achieved by PtSi alloying with Hf [8].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…PtSi is a promissing contact material for PMOS source and drain, because of its excellent thermal stability, low Si consumption and low SBH for hole. However, the barrier height for electron (Φ Bn ) is 0.87 eV, which is relatively high compared to that of NiSi [3,5]. PtSi alloying with low work function metal is a promissing process to reduce Φ Bn , and we have reported that a 0.3 eV reduction of Φ Bn , was achieved by PtSi alloying with Hf [8].…”
Section: Introductionmentioning
confidence: 94%
“…Some researchers reported that Yb incorporation to NiSi reduced the Φ Bn of NiSi effectively [10,11]. In this paper, reducing the Φ Bn of PtSi by alloying with Yb was investigated [8], and the silicidation mechanism was proposed for the first time.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The addition of rare earth material such as Ytterbium 16,17 or Dysprosium 17,18 (Dy) to Ni followed by silicidation has also been demonstrated to give U B n,eff below 0.65 eV. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A second approach is to reduce the effective SBH for electrons by implanting with Se, S, Te or Al and thermally driving the implanted species to the silicide/silicon interface [4][5][6]. A third technique is to reduce the work function by using rare-earth metal silicides or by incorporating additional elements into the silicide [7]. Similar concepts apply for PMOS ρ c reduction.…”
mentioning
confidence: 99%